2007
DOI: 10.1159/000104759
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Retinal Nerve Fiber Layer Thickness in Patients with Pseudoexfoliation Syndrome Using Optical Coherence Tomography

Abstract: Objective: To evaluate the retinal nerve fiber layer (RNFL) thickness in patients with unilateral pseudoexfoliation syndrome (PXS) without glaucoma by using optical coherence tomography (OCT). Methods: 22 patients with unilateral PXS were evaluated. Group 1 included the eyes with the pseudoexfoliation, group 2 included the fellow eyes; 18 age-matched normal control eyes were assessed in group 3. The mean and segmental RNFL thickness in eyes with pseudoexfoliation and their fellow eyes in patients with unilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 49 publications
4
30
0
1
Order By: Relevance
“…Three studies were performed in Turkey [10,12,22] , and one each was performed in Cairo [11] , Pakistan [6] Iran [13] India [7] , and Greece [21] . The mean age of the patients in each study ranged from 54 to 71 years, and the percentage of men ranged from 25 to 94%.…”
Section: Characteristics and Quality Of The Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were performed in Turkey [10,12,22] , and one each was performed in Cairo [11] , Pakistan [6] Iran [13] India [7] , and Greece [21] . The mean age of the patients in each study ranged from 54 to 71 years, and the percentage of men ranged from 25 to 94%.…”
Section: Characteristics and Quality Of The Studiesmentioning
confidence: 99%
“…In addition, the results of studies using optical coherence tomography (OCT) to compare RNFL thickness in 4 quadrants between PXS patients and healthy controls have been inconsistent. While it has been reported that the RNFL in patients with PXS is significantly thinner than in controls in all quadrants except the nasal quadrant [10,11] , other studies have reported that RNFL thickness is reduced only in the inferior quadrant [6,12] . Additionally, one study found that the average thickness of all quadrants was significantly lower than in controls, but there was no significant reduction when quadrants were looked at individually [13] .…”
Section: Introductionmentioning
confidence: 97%
“…Many researchers have also observed a statistically significantly higher IOP in patients with PEX compared to the control group. 2,3,15,17,18 Klemetti et al pointed out that the initial average IOP in eyes with PEX is important in the conversion from PEX to PEXG. They noticed that the eyes with PEX which developed ocular hypertension or glaucoma later in the course of disease had had a significantly higher IOP (p < 0.001) compared to the eyes in which there was no development of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Yüksel et al (4) . assessed the RNFL thickness in patients with unilateral PXS without glaucoma and their normal fellow eyes using Stratus OCT-3.…”
Section: Discussionmentioning
confidence: 99%